2023
DOI: 10.1177/10949968231194905
|View full text |Cite
|
Sign up to set email alerts
|

The Power of AI-Generated Voices: How Digital Vocal Tract Length Shapes Product Congruency and Ad Performance

Fotis Efthymiou,
Christian Hildebrand,
Emanuel de Bellis
et al.

Abstract: Can AI-generated voices be designed to improve product and brand perceptions? Akin to human voices that evoke mental images in a listener even without visual cues, artificially generated voices can be intentionally designed to elicit envisioned mental representations. Drawing from prior work on sound symbolism and computational advances in speech synthesis, the authors explore how the voice of an AI-powered conversational agent (e.g., a voice assistant such as Amazon Alexa) impacts consumer perceptions and cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Additionally, AI generated voices and/or voice clones can be easily modified to speak in another language or with another dialect, while maintaining the essence of the personality of the original. Efthymiou et al (2023) demonstrated that manipulating the vocal tract length (i.e., timbre) of a synthetic voice had an impact on perceptions of congruency toward stereotypically masculine and feminine products, which in turn improved click-through rates and lowered costs per click. AI technology may also aid in combining or morphing voices in unique ways, and at least one study suggests that 15 Brand voices may be human/celebrity driven (e.g., Dennis Haysbert for Allstate, James Earl Jones for CNN, Josh Lucas for The Home Depot) or character driven (e.g., the Geico Gecko, the AFLAC duck, Mayhem for AllState).…”
Section: Ai and Sonic Brandingmentioning
confidence: 99%
“…Additionally, AI generated voices and/or voice clones can be easily modified to speak in another language or with another dialect, while maintaining the essence of the personality of the original. Efthymiou et al (2023) demonstrated that manipulating the vocal tract length (i.e., timbre) of a synthetic voice had an impact on perceptions of congruency toward stereotypically masculine and feminine products, which in turn improved click-through rates and lowered costs per click. AI technology may also aid in combining or morphing voices in unique ways, and at least one study suggests that 15 Brand voices may be human/celebrity driven (e.g., Dennis Haysbert for Allstate, James Earl Jones for CNN, Josh Lucas for The Home Depot) or character driven (e.g., the Geico Gecko, the AFLAC duck, Mayhem for AllState).…”
Section: Ai and Sonic Brandingmentioning
confidence: 99%